The Thucydidean Legacy of Systemic Geopolitical Analysis and Structural Realism - Ioannis Mazis; Markos Troulis; Xanthippi Domatioti (International Journal of Humanities and Social Science Invention, 2019)
Which are the modern roots of the theories of Systemic Geopolitical Analysis and Structural Realism? Which are the epistemological and methodological bases that a conflict is profound? Being descriptive theories, both Systemic Geopolitical Analysis and Structural Realism have been constructed on the basis of axial hypotheses tested through historical practical case studies. They represent complementary approaches, based on the common Thucydidean legacy of description and analysis emphasizing ontology. In the modern framework of scientific debate, there are also common roots, while the commonalities are more between them in comparison with other theoretical approaches even included in the same scientific field. Under this lens, the current paper endeavors to decode all those reasons making the two theoretical approaches two – even not identical – twins of Thucydides.